(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the single electron transistors are extremely sensitive devices as position detectors for nanoelectromechanical systems. Suspended carbon nanotubes have observed a reduction of the mechanical resonance frequency of the fundamental bending at low bias voltages near the degenerate region. This effect is a precursor of the mechanical instability and thus of the current blockade. We have found that the consequence of a capacitive electromechanical coupling in a suspended single electron transistor when the supporting beam is brought close to the Euler buckling instability by a lateral compression force. The result is that the low bias current blockade originating from the coupling between the electronic degrees of freedom and the classical resonator enhanced by several orders of magnitude in the vicinity of the instability. These results are a direct consequence of the continuous nature of the Eular buckling instability and the associated critical slowing down of the fundamental bending mode of the beam at the instability. Our results frequently have close and instructive analogies with mean field theory of second order phase transitions. In order to increase energy, we can increase the electrostating coupling between the oscillator and the single electron transistor, since energy depends quadratically on electrostatic force and a large change in the gate voltage is found when electrons tunnel. In the way of reducing oscillator spring constant in a controlled manner is to operate a doubly clamped beam subject to a lateral compression force. Under the action of the lateral compression force the system exhibited a continuous transition from a flat to a blockade state, while the fundamental bending mode became softer as approached the mechanical instability. We have found that near the buckling instability the current blockade induced by the mechanical resonator is strongly enhanced, rendering this effect. The obtained results were found in good agreement with previously obtained results.